A quantitative analysis of the relationship of franchise value, implicit insurance and bank stability. (1st January 2014) - Qu, Hongjian; Liang, Zhou; Qian, Huimin
Recent studies have shown that endogenous self-regulatory effect of franchise value can improve bank stability. In order to test the endogenous self-regulation effect of Chinese commercial bank's recessive insurance system, this paper builds an econometric model which consists of franchise value, recessive insurance and bank stability, and then completes an empirical analysis through 16 listed Chinese commercial banks' unbalanced panel data during 2000–2011. The empirical results show that the self-regulatory effect of endogenous franchise value does exist; the recessive insurance covers all types of commercial banks. The recessive insurance system weakens the role of self-regulation of endogenous franchise value. The larger scale of the bank, the better robustness, government regulation enhances the stability of banks; Chinese listed commercial banks' capital leverage and operating leverage effect is not fully effective.